Transwell Culture with Adipose Tissue-Derived Stem Cells and Fertilized Eggs Mimics the In Vivo Development of Fertilized Eggs to Blastocysts in the Fallopian Tube: An Animal Study - Toyofumi Hirakawa; Kazuhiko Nakabayashi; Noriko Ito; Kenichiro Hata; Shiori Imi; Mami Shibata; Daichi Urushiyama; Kohei Miyata; Fusanori Yotsumoto; Shin'ichiro Yasunaga; Tsukasa Baba; Shingo Miyamoto (MDPI AG, 2024)
Many countries, including Japan, are experiencing declining birth rates. Assisted reproductive technologies have consistently demonstrated good results in resolving infertility. Although the development of fertilized eggs into blastocysts has been recognized as a crucial step in assisted reproductive technologies, the involved mechanisms are currently unclear. Here, we established a new culture system for the in vitro development of fertilized eggs into blastocysts. In the Transwell culture system, the rate of blastocysts hatching from fertilized eggs cultured with adipose-derived stem cells (ASCs) was significantly higher than that of blastocysts cultured only with fertilized eggs. Gene ontology analysis revealed that the developed blastocysts displayed essential gene expression patterns in mature blastocysts. Additionally, when cultured with 3rd-passage ASCs, the developed blastocysts expressed the core genes for blastocyst maturation and antioxidant properties compared to those cultured only with fertilized eggs or cultured with 20th-passage ASCs. These results suggest that the Transwell culture system may imitate the in vivo tubal culture state for fertilized eggs. Exosomes derived from stem cells with stemness potential play a powerful role in the development of blastocysts from fertilized eggs. Additionally, the exosomes expressed specific microRNAs; therefore, the Transwell culture system resulted in a higher rate of pregnancy. In future, the extraction of their own extracellular vesicles from the culture medium might contribute to the development of novel assisted reproductive technologies.